2000
DOI: 10.1163/22941932-90000248
|View full text |Cite
|
Sign up to set email alerts
|

Wood Characteristics of Amazon Forest Types

Abstract: The Tambopata region of the southern Peruvian Amazon supports a high diversity of both woody plants and forest types. Woods collected from low riverside vegetation, floodplain forest, clay-soil forest on an upper terrace, sandy-soil forest, and swamp forest provide an opportunity to test for significant differences in quantitative anatomical characters among forest types. Vessel-element length in floodplain-forest trees is significantly greater than in the other forest types. Specific gravity is lower in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(47 reference statements)
2
8
0
2
Order By: Relevance
“…On a global scale, vessel diameters tend to increase with decreasing latitude, that is, in warmer regions (Baas 1986). Woodcock et al (2000) found very large vessel diameters (>200 µm) and only a few narrow vessels in trees from the Amazon forest where temperatures do not fall below 0°C. However, even in tropical regions there is an upper limit for a useful vessel diameter.…”
Section: Ecological Trendsmentioning
confidence: 91%
“…On a global scale, vessel diameters tend to increase with decreasing latitude, that is, in warmer regions (Baas 1986). Woodcock et al (2000) found very large vessel diameters (>200 µm) and only a few narrow vessels in trees from the Amazon forest where temperatures do not fall below 0°C. However, even in tropical regions there is an upper limit for a useful vessel diameter.…”
Section: Ecological Trendsmentioning
confidence: 91%
“…There have already been several reports of variations with site/growth conditions of order 10% for plantation tropical tree species (Roque, 2004;Erskine et al, 2005). Similarly, site specific differences have been noted when comparing the same species growing in different forests or site conditions (Gonzalez and Fisher, 1998;Woodcock et al, 2000;Muller-Landau, 2004;Parolin and Ferreira, 2004;Roque, 2004;Nogueira et al, 2005;Nogueira et al, 2007). Lower D w is often associated with early and secondary succession vegetation (Saldarriaga 1989;Woodcock et al, 2000) and higher growth rates (Wiemann and Williamson, 1989;Erskine et al, 2005;Nogueira et al, 2005;King et al, 2005King et al, , 2006.…”
Section: Introductionmentioning
confidence: 90%
“…Tais características são consideradas importantes para o desempenho das funções do xilema em condições ambientais diversas e expressam as tendências ecológicas em gradientes latitudinais e altitudinais em diferentes macro e mesoclimas (p. ex. Baas et al 1983;Dickison 1989;Woodcock et al 2000). Wheeler & Baas (1991) utilizando o modelo proposto por Dickison (1989) e a literatura disponível, relacionaram as tendências ecológicas gerais para hábitats xéricos, montanos e tropicais.…”
Section: Introductionunclassified